Forever, or a long, long time - Carter, Caela (Harper, 2019)
Eleven-year-old Flora and her younger brother have been bounced from one foster home to the next as long as they can remember. Their memories of childhood are so scattered, they lack a sense of history. Without this sense of permanence. Flora struggles to comprehend that her adoption by her new family means she's found her forever home--what does forever mean to a child who feels as if she were dropped into the world without roots? Understanding this, their adoptive mother takes them back in time to their former foster homes so they might be able to embrace their future.